International Conference on Oriental Thinking and Fuzzy Logic Celebration of the 50th Anniversary in the era of Complex Systems and Big Data - Cao, Bing-Yuan; Wang, Pei-Zhuang; Liu, Zeng-Liang; Zhong, Yu-Bin (Advances in Intelligent Systems and Computing,, 2016)
This proceedings book presents edited results of the eighth International Conference on Fuzzy Information and Engineering (ICFIE'2015) and on Oriental Thinking and Fuzzy Logic, in August 17-20, 2015, in Dalian, China. The book contains 65 high-quality papers and is divided into six main parts: "Fuzzy Information Processing", "Fuzzy Engineering", "Internet and Big Data Applications", "Factor Space and Factorial Neural Networks", "Information Granulation and Granular Computing" as well as "Extenics and Innovation Methods".